Epidemiological and entomological profile of malaria in Huambo province. Angola, 2018 - Lourdes Elena Duany Badell; Clementino Sacanombo; Jovita Chocoputo Cachequele André; Mwadi Kapinga Kapinga; Jesús Ramón Joya Garcia; Joaquin Ukuessenje Isaac (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: Malaria is a life-threatening disease. In a non-immune individual, symptoms usually appear between 10 and 15 days after the infective mosquito bite. It is important to know its entomo-epidemiological profile, especially in areas where it is very common. Objective: to describe the entomo-epidemiological profile of malaria in Huambo province during 2018. Methods: a descriptive, retrospective cross-sectional study was carried out. Variables studied: malaria cases, number of deaths, age, infected pregnant women, method of diagnosis and focal point. For data collection, the database of the National Epidemiology Directorate was used and they were processed with SPSS, version 15.0. Results: there was a marked decrease in cases and deaths during the year; those under five years of age reported higher rates of morbidity and mortality; pregnant women are one of the most vulnerable groups; the 65.5% of those diagnosed with malaria underwent a rapid test and there was a decrease in larval populations as a result of the use of the Bactivec and Gliceresf Cuban insecticides. Conclusions: malaria is a health problem in Huambo, its burden is high and causes great morbidity and fatality rates in vulnerable groups such as pregnant women and children under five years of age.